Strategi Peningkatan Branding Produk Umkm Kopi Murni Pak Tuwo Menggunakan Media Sosial Instagram - Dammandtyo Tegar Samudra; Acep Samsudin (Yayasan Daarul Huda Kruengmane, 2023)
Strong branding is crucial for SMEs in enhancing visibility, brand awareness, and customer loyalty. This research aims to understand how Kopi Murni Pak Tuwo, an SME, can leverage Instagram as a strategic tool to strengthen their branding. The research methodology employed in this journal is a case study, involving Kopi Murni Pak Tuwo as the research subject. Data was collected through interviews with the business owner and direct observation of the branding activities conducted through their Instagram account. Additionally, surveys were also conducted among customers who follow the SME's Instagram account. The research findings indicate that using Instagram as a branding platform can provide significant benefits for Kopi Murni Pak Tuwo. In this regard, Instagram enables them to expand their market reach, build interactions with customers, and establish a consistent brand image. Engaging visual content, relevant hashtag usage, and active interaction with Instagram followers have proven to be effective in strengthening the branding of this SME. In conclusion, this research proposes several strategies that can be employed by Kopi Murni Pak Tuwo and similar SMEs to enhance their branding through Instagram. These strategies include the use of compelling visual content, relevant brand-related hashtags, utilizing the Stories feature to provide unique content, and active engagement with followers and customers. It is hoped that this journal can provide insights and practical guidance for SMEs in leveraging Instagram as an effective branding tool.